FINANCIAL LEVERAGE, PROFITABILITAS DAN NILAI PERUSAHAAN (STUDY PADA INDUSTRI MAKANAN DAN MINUMAN DI INDONESIA) - Ni Luh Anik Puspa Ningsih; Ni Wayan Eka Novia (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The establishment of a business has long-term goals, sustainability and maximizing firm value. The food and beverage industry is required to be able to compete and have an optimal performance which is reflected in the firm value. This is one aspect that is used as a benchmark for investors in assessing a company. Firm Value is influenced by various financial factors including financial leverage and profitability. The aim of this study is to analyze the maximization firm value through financial leverage and profitability in the food and beverage industry on the Indonesia Stock Exchange. The population of this study is all companies listed in the food and beverage industry on the Indonesia Stock Exchange for the period 2017 – 2021 as many as 26 companies. Using the purposive sampling method, the research sample was obtained as many as 15 companies. The method of collecting data is by documentation study so that secondary data is obtained from the official website of the Indonesia Stock Exchange. The analytical technique of this research is multiple linear regression and found that financial leverage and profitability individually have a positive and significant effect on the firm value of the Food and Beverage Industry companies listed in the Indonesia Stock Exchange.